Polymorphisms within the COL5A1 gene and regulators of the extracellular matrix modify the risk of Achilles tendon pathology in a British case-control study. Issue 15 (3rd August 2017) - Brown, Karryn L.; Seale, Kirsten B.; El Khoury, Louis Y.; Posthumus, Michael; Ribbans, William J.; Raleigh, Stuart M.; Collins, Malcolm; September, Alison V.
ABSTRACT: Several genetic loci have been associated with risk of Achilles tendon pathology (ATP) within South African and Australian populations. The aim of this study was, therefore, to evaluate eight previously implicated genetic variants in an independent British population. A total of 130 asymptomatic controls (CON) and 112 participants clinically diagnosed with ATP comprising 87 individuals with chronic Achilles tendinopathy (TEN) and 25 with Achilles tendon ruptures (RUP) were included. All participants were genotyped for variants within the COL5A1, MIR608, IL-1β, IL-6 and CASP8 genes. Primary findings implicated COL5A1 and CASP8 . Three inferred allele combinations constructed from COL5A1 rs12722, rs3196378 and rs71746744 were identified as risk modifiers. The T–C–D combination was associated with increased risk of ATP ( P = 0.023) and RUP ( P < 0.001), the C–A–I combination was associated with increased risk of ATP ( P = 0.011), TEN ( P = 0.011) and RUP ( P = 0.011) and the C–C–D combination was associated with decreased risk of ATP ( P = 0.011) and RUP ( P = 0.004). The CASP8 rs3834129 DD genotype was associated with decreased risk of TEN ( P = 0.020, odds ratio: 0.45, 95% confidence interval: 0.22–0.90) and the CASP8 I–G (rs3834129–rs1045485) inferred allele combination was associated with increased risk of TEN ( P = 0.031). This study further highlights the importance of polymorphisms within COL5A1 and CASP8 in the aetiology of ATP.